Outcome of patients with coronary artery disease on regular haemodialysis - Wan Ali, Wan Ahmad Syahril Rozli; Seman, Mohd Ramli; Draman, Che Rosle; Shahar, Mohammad Arif (2013)
Background: Heart disease is among the leading cause of mortality in haemodialysis patients. Of the cardiovascular deaths, about 20 percent is associated with coronary artery disease (CAD). Objective: To analyze the characteristics and outcomes of patients with coronary artery disease on regular haemodialysis. Methods: In this retrospective cohort study, fourty four patients with ischemic heart disease undergoing regular haemodialysis in the state of Pahang from the year 2005 until 2012 were assessed. The relationship between disease characteristics and dialysis adequacy were assessed. Results: The majority of the patients were males ( 70.5% ). The mean age was 58.7 + 8.9 years old (95% CI 56.0-61.0). Diabetic nephropathy was the commonest cause of ESRD (68.2%). The mean duration of haemodialysis was 57.2 + 38.6 months (95% CI 45.4 – 68.9). Five (11.4%) of the patients were having recurrent angina, and ten (22.2%) died during the course of treatment. The initial intradialytic hypotension were reported in 16 (36%) patients. Thirty three (75%) patients have undergone coronary angiography. Nine (20.5%) patients undergone coronary stenting, and fourteen (31.8%) have coronary artery bypass grafting. The mean kT/V and Qb were 1.50 + 0.3 (95% CI 1.4-1.6) and 306 + 42.6 ml/min (95% CI 293-319) respectively. Most of the patients (88.6%) have adequate kT/V of above 1.2, and 42 (95.5%) have Qb of more than 300ml/min. Other parameters for dialysis adequacy like haemoglobin and albumin level were measured with a mean of 10.3 + 1.8 g/dL (95% CI 9.7-10.9) and also 40.8 + 6.5mmol/l (95% CI 38.2-42.1) respectively. The 1-year and 5-years survival rate of patients in this cohort are 95% and 75% respectively, with a mean survival of 123.3 + 10.9 months (95% CI 101.9-144.6). Conclusion: The cumulative 5-year survival is better in this cohort compared to other similar studies . Despite the underlying CAD, patients received adequate haemodialysis based on the parameters measured. Despite poorer long term outcomes, patients with CAD may be put on haemodialysis provided the treatment of the underlying condition has been fully optimized. References : - Coronary artery disease as a definitive risk factor of short-term outcome after starting dialysis in diabetic renal failure patients. Joki N et.al.,Clin Nephrol.2001 Feb ;55(2):109-14. - Mortality differences by dialysis modality among incident ESRD patients with and without coronary artery disease. Ganesh SK et.al., J Am Soc Nephrol. 2003 Feb ;14(2):415-24. Key Words: Coronary artery disease, Haemodialysis